Stacking disease resistance and mineral biofortification in cassava varieties to enhance yields and consumer health. Issue 4 (10th December 2020) - Narayanan, Narayanan; Beyene, Getu; Chauhan, Raj Deepika; Grusak, Michael A.; Taylor, Nigel J.
Summary: Delivering the benefits of agricultural biotechnology to smallholder farmers requires that resources be directed towards staple food crops. To achieve effect at scale, beneficial traits must be integrated into multiple, elite farmer‐preferred varieties with relevance across geographical regions. The staple root crop cassava ( Manihot esculenta ) is consumed for dietary calories by more than 800 million people, but its tuberous roots provide insufficient iron and zinc to meet nutritional needs. In Africa, cassava yields are furthermore limited by the virus diseases, cassava mosaic disease (CMD) and cassava brown streak disease (CBSD). In this study, we strove to develop cassava displaying high‐level resistance to CBSD and CMD to attain food and economic security for cassava farmers, along with biofortified levels of iron and zinc to enhance consumer health. RNAi‐mediated technology was used to achieve resistance to CBSD in two East African and one Nigerian farmer‐preferred cultivars that harboured resistance to CMD. The Nigerian cvs. TMS 95/0505 and TMS 91/02324 were modified with T‐DNA imparting resistance to CBSD, along with AtIRT1 (major iron transporter) and AtFER1 (ferritin) transgenes to achieve nutritionally significant levels of iron and zinc in cassava storage roots (145 and 40 µg/g dry weight, respectively). The inherent resistance to CMD was maintained in all four disease resistant and mineral enhanced cassava cultivars described here, demonstrating that this technique could be deployed across multiple farmer‐preferred varieties to benefit the food and nutritional security of consumers in Africa.